2019
DOI: 10.3390/su11040993
|View full text |Cite
|
Sign up to set email alerts
|

Disaster-Recovery Social Capital and Community Participation in Earthquake-Stricken Ya’an Areas

Abstract: Social capital plays a significant role in post-disaster community participation and disaster recovery. This study divides social capital into three aspects: Cognition, structure, and relation, and discusses the impact of these factors on community participation in post-disaster recovery. Through data analysis, we found that a self-organized relationship villager network had a positive effect on villagers’ participation in voluntary community activities after an earthquake, while the local cadre relationship n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…This study supports existing literature suggesting an iterative and positive link between social capital and community disaster resilience, manifested through collective action. Similar findings have been documented in diverse cases e.g., (Woolcock 1998 ; Larsen et al 2004 ; Bolte and Eucker 2012 ; Aldrich and Meyer 2015 ; Sadri et al 2017 ; Chan et al 2018 ; Wei and Han 2018 ; Li and Tan 2019 ). Future work would benefit from exploring, not if there is a relationship, but the role of context in shaping the degree of and nuances of the relationship.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study supports existing literature suggesting an iterative and positive link between social capital and community disaster resilience, manifested through collective action. Similar findings have been documented in diverse cases e.g., (Woolcock 1998 ; Larsen et al 2004 ; Bolte and Eucker 2012 ; Aldrich and Meyer 2015 ; Sadri et al 2017 ; Chan et al 2018 ; Wei and Han 2018 ; Li and Tan 2019 ). Future work would benefit from exploring, not if there is a relationship, but the role of context in shaping the degree of and nuances of the relationship.…”
Section: Discussionsupporting
confidence: 83%
“…Engaging in shared experiences, actions and activities seems to be a general feature that fosters social capital formation, mostly bonding and bridging ties. Either shared physical activities or cognitive shared experiences seem to be key, in ways that make sense in the community context e.g., (Taylor 2011 ; Gallagher et al 2019 ; Li and Tan 2019 ; Shimpo et al 2019 ). However, developing policies that do this in other places in ways that make sense locally, remains a substantial gap between what the literature says is beneficial and what can be done about it proactively and perhaps preventively for disaster resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, utilities and local governments should facilitate community engagement on an ongoing basis to obtain their buy-ins and ensure a smooth recovery process from potential wildfires in the future. In this context, various studies on the importance of social capital and community engagement in the recovery process for floods [168], earthquakes [169], hurricanes [170], and wildfires [171][172][173] are presented in the literature. A systematic literature review on community engagement for disaster preparedness can be found in [174].…”
Section: Community Engagementmentioning
confidence: 99%
“…Learning is strongly associated with discovery and hence requires self-regulation. Learning also takes the forms of the building of conceptual structures through reflection and abstraction (Weibell 2011;Schunk 2012;Lefrançois 2019). One of the most influential constructivist theorists is Dewey (1933).…”
Section: Cognitive Constructivismmentioning
confidence: 99%